Beyond the Situation: Hanging Out with Peers now is Associated with Short-Term Mindsets Later - Kübel, Sebastian L. (Journal of developmental and life-course criminology, 2024)
It is well-established that unstructured unsupervised socializing with peers (UUS) motivates deviance while in that specific context. In this article, we extend this situational view by arguing that repeated UUS may also gradually shape adolescents’ norms and decision making beyond the situation. Specifically, we argue that UUS promotes short-term mindsets, i.e., an increased focus on present rewards at the expense of considering future consequences. We test this hypothesis with fixed-effects models, using longitudinal data from a representative sample of 1,675 adolescents from Zurich, Switzerland. Consistent with our preregistered predictions, more frequent UUS is associated with increased short-term mindsets. Thus, our finding suggests that the effects of UUS on later deviance might be driven by becoming more present-oriented. This link offers new insights into the developmental pathways toward adolescent delinquency and offers a potential target for intervention.